Building Gen Z Entrepreneurial Motivation and Confidence in Bekasi through Social Media, Risk Perception, and Social Support - Jasmine Fathiya Arifin; Diah Pranitasari; Rifaldi Nurul Akbar; Taufiq Ramadhan (Jurnal Manajemen Pendidikan, 2025)
Background: The increasing interest in entrepreneurship among Generation Z, particularly in developing regions such as Bekasi, raises questions about the factors shaping their entrepreneurial motivation and confidence in the digital era. Understanding these influences is essential for fostering young entrepreneurs. Purpose: This study aims to examine the influence of social media, risk perception, and social support on the entrepreneurial motivation and confidence of Generation Z in Bekasi. Design/method/approach: A quantitative approach using path analysis was employed, involving 325 Generation Z respondents aged 18-29 years in Bekasi. Data were collected through a Likert-scale questionnaire and analyzed using SmartPLS 4.0. The analysis included outer model tests (convergent validity, discriminant validity, composite reliability, and Cronbach’s alpha), inner model tests (path coefficient and goodness of fit), and hypothesis testing. Results: The findings indicate that social support and risk perception have a direct and significant effect on entrepreneurial motivation, while social media does not. Entrepreneurial motivation also serves as a strong mediator, through which social support and risk perception indirectly influence entrepreneurial confidence. Contribution/value: This study contributes to the understanding of entrepreneurial behavior among Generation Z by highlighting the mediating role of motivation and the relative insignificance of social media, offering insights for educators, policymakers, and entrepreneurial programs targeting youth.